Civic engagement in American democracy - Skocpol, Theda; Fiorina, Morris P. (Brookings Institution Press ; Russell Sage Foundation, 1999)
"Civic Engagement in American Democracy opens with an eagle's-eye view of the roots of America's special patterns of civic involvement, examining the way social groups and government and electoral politics have influenced each other over the last 200 years. Other chapters explore community politics, the electoral process, religious institutions, and the advantages and disadvantages of contemporary advocacy politics. The book also probes the influence of long-term social and cultural changes on voluntary associations and civic participation."--BOOK JACKET. Title Summary field provided by Blackwell North America, Inc. All Rights Reserved